Comparative Study of Morphology and Histology on Papuan Jellyfish Mastigias papua in Kakaban Lake and Sea - Nurasmi Nurasmi; Ahmad Ridwan; Awaludin Awaludin (Journal of Tropical Life Science, 2021)
Jellyfish are marine invertebrates belonging to the phylum Cnidaria. Papua Mastigias is a jellyfish from the Scyphozoa class. This study aims to observe differences in the differences in environmental parameters, morphology and shape of nematocyte cells using the histological method with (SEM) Scanning Electron Microscopy on Papua Mastigias jellyfish in the Kakaban Lake and Sea. Environmental parameters in Lake Kakaban and Sea Kakaban were measured for salinity, temperature, and pH. The results of the t-test analysis showed that there were significant differences in environmental parameters in Lake Kakaban and Sea Kakaban (p <0.05). Body diameter and length of jellyfish tentacles were measured and analyzed using SPSS 16 with a t-test. From the t-test analysis, results showed that for Mastigias Papua jellyfish in Lake Kakaban and jellyfish in the Kakaban Sea showed a significant difference in the diameter and length of the body tentacles (p <0.05). The SEM results of jellyfish in the Kakaban Sea showed that the tentacles of Mastigias Papua in the Kakaban Sea had nematocytes consisting of three forms, namely Microbasic isorhiza, Atrichouz isorhiza, and Merotrichous isorhiza. Mastigias Papua in Lake Kakaban has nematocyst cells, which comprise of one type, namely Microbasic mastigophoran, where the number of nematocytes is minimal and has a smaller size than the Papuan Mastigias jellyfish that live in the Kakaban Sea. Nemeatocyte cells are stinging cells in jellyfish. SEM results show that the jellyfish in Lake Kakaban cannot sting because the size of the jellyfish tentacles is reduced to smaller, fewer nematocyte cells and different shape nematocytes. Based on the results of this study, it can be concluded that there are differences in environmental parameters, body dimensions, tentacle length, and the size and number of nematocytes between Mastigias Papua jellyfish in Dunau and in the Kakaban Sea.